ACADEMIC PROCRASTINATION: EXAMINING THE CONTRIBUTION OF PEER CONFORMITY AND SELF CONCEPT VARIABLES - Nur Saqinah Galugu; Hasbia Kaso; Nasriandi (Educouns Journal: Jurnal Pendidikan dan Bimbingan Konseling, 2021)
Academic procrastination is Deliberate and repetitively delay in completing test or activity. This is a quantitative research to examine the contribution of peer conformity and self cocept towards academic procrastination.  70 students from 8th grade at Junior high school number 6 palopo were selected as the sample of this research  by using random sampling. The result of this research shows that peer conformity and self concept have significant contribution towards Students' academic procrastination.